2020
DOI: 10.5005/jp-journals-10005-1806
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of Triphala and Propolis-modified Glass Ionomer Cement: An In Vitro Study

Abstract: A bstract Background The antimicrobial activity of restorative materials has a major role in preventing recurrent caries. Aim To assess the antimicrobial activity of triphala and propolis-modified glass ionomer cement (GIC) against Streptococcus mutans and Lactobacillus . Materials and methods The samples were prepared using cylindrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(14 reference statements)
0
1
0
1
Order By: Relevance
“…However, challenges persist in their use as restorative materials, including susceptibility to secondary caries and low mechanical properties. Recent studies indicate that the fluoride-releasing capability of conventional GICs may be insufficient for effective antibacterial conservation in many cases [ 17 ]. Consequently, various efforts have been made to enhance the antibacterial properties of GICs to prevent secondary caries.…”
Section: Discussionmentioning
confidence: 99%
“…However, challenges persist in their use as restorative materials, including susceptibility to secondary caries and low mechanical properties. Recent studies indicate that the fluoride-releasing capability of conventional GICs may be insufficient for effective antibacterial conservation in many cases [ 17 ]. Consequently, various efforts have been made to enhance the antibacterial properties of GICs to prevent secondary caries.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to acidic challenges is crucial in ensuring the long-term durability of materials used in direct restorations. It has been shown that acidic conditions can have detrimental effects on tooth structure and restorative materials [ 13 ]. While adding antimicrobial agents to dental materials provides several therapeutic benefits, it frequently affects their physio-mechanical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…11 Beberapa penelitian menunjukkan bahwa penambahan ekstrak etanol propolis (EEP) mampu meningkatkan efek antibakteri SIK. [12][13][14] Di sisi lain, modifikasi ini memiliki dampak negatif terhadap sifat mekanik SIK, seperti pengaruhnya dalam penurunan kekuatan tekan semen. 13,15 Diketahui bahwa modifikasi ini juga memengaruhi sifat fisik material, di antaranya mengurangi viskositas serta memperpanjang waktu kerja dan waktu pengerasan SIK.…”
Section: Pendahuluanunclassified